A neglected neurodegenerative disease: Adult-onset globoid cell leukodystrophy - Wu, Guode; Li, Zhenhua; Li, Jing; Li, Xin; Wang, Manxia; Zhang, Jing; Liu, Guangyao; Zhang, Pengfei (Frontiers in Neuroscience, 2022)
Globoid cell leukodystrophy (GLD), or Krabbe disease (KD) is a rare neurodegenerative disease, and adult-onset GLD is more even neglected by clinicians. This review provides detailed discussions of the serum enzymes, genes, clinical manifestations, neuroimaging features, and therapies of GLD, with particular emphasis on the characteristics of adult-onset GLD, in an attempt to provide clinicians with in-depth insights into this disease.